Effect of pre-cooling on repeat-sprint performance in seasonally acclimatised males during an outdoor simulated team-sport protocol in warm conditions - Brade, Carly; Dawson, B.; Wallman, K. (2013)
Whether precooling is beneficial for exercise performance in warm climates when heat acclimatised is unclear. The purpose of this study was to determine the effect of precooling on repeatsprint performance during a simulated team-sport circuit performed outdoors in warm, dry field conditions in seasonally acclimatised males (n = 10). They performed two trials, one with precooling (PC; ice slushy and cooling jacket) and another without (CONT). Trials began with a 30-min baseline/cooling period followed by an 80 min repeat-sprint protocol, comprising 4 x 20-min quarters, with 2 x 5-min quarter breaks and a 10-min half-time recovery/cooling period. A clear and substantial (negative; PC slower) effect was recorded for first quarter circuit time. Clear and trivial effects were recorded for overall circuit time, third and fourth quarter sprint times and fourth quarter best sprint time, otherwise unclear and trivial effects were recorded for remaining performance variables. Core temperature was moderately lower (Cohen's d=0.67; 90% CL=-1.27, 0.23) in PC at the end of the precooling period and quarter 1. No differences were found for mean skin temperature, heart rate, thermal sensation, or rating of perceived exertion, however, moderate Cohen's d effect sizes suggested a greater sweat loss in PC compared with CONT. In conclusion, repeat-sprint performance was neither clearly nor substantially improved in seasonally acclimatised players by using a combination of internal and external cooling methods prior to and during exercise performed in the field in warm, dry conditions. Of practical importance, precooling appears unnecessary for repeat-sprint performance if athletes are seasonally acclimatised or artificially acclimated to heat, as it provides no additional benefit. © Journal of Sports Science and Medicine.